Pulmonary embolism: Analysis of compartmentalisation by plication - Larre Borges, Uruguay; Del Campo, Alberto; Delgado, Fernando; Vidal, Hugo (Cirugía del Uruguay, 1971)
This is an evaluation of the method which consist of plication of the inferior vena cava for treatment of pulmonary thromboembolism. lt is based on experiments carried out in animals which consist of creating a state of hyperthrombicity and using radiopaque emboli.